Determinants of Malaysian palm oil export efficiency: A Gravity Stochastic Frontier Model - Syajarul Imna Mohd Amin,; Md Shafiin Shukor,; Aisyah Abdul-Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Palm oil export is one of the significant contributors to the Malaysian economy. The country's palm oil export is affected by international market uncertainties. This study examines the determinants of Malaysian palm oil export efficiency from 2000 to 2020. The Gravity Stochastic Frontier Model (GSFM) findings show that importing countries' GDP and foreign exchange rates positively affect Malaysian palm oil export. In contrast, distance has a negative impact on palm oil export. The study also found that technical efficiency increased from 2000 to 2020. Meanwhile, the average export efficiency score was high except for the US. This study enriches the agricultural literature, especially concerning palm oil export in Malaysia. Thus, the findings enlighten the industry and policymakers in formulating policies that can improve palm oil export and its competitiveness at the global level.